Avaliação dos efeitos antioxidantes e anti-genotóxicos in vivo da semente de linum usitatissimum l. - (:unkn) unknown (Universidade Federal do Pampa, 2013)
Plants are considered the best source of natural antioxidants. Among them, a functional food widely used is flaxseed (Linum usitatissimum L.). Flaxseed is composed mainly of minerals, vitamins, proteins and lipids. Additionally, contain significant amounts of bioactive compounds such as polyphenols, polyunsaturated fatty acids, fibers and lignans. It is reported that a meal containing flaxseed has a high nutritional potential, not only for protein content, but also by the amount of soluble fiber and lignans. The popular use is on the rise, however, there are few studies involving humans. The objective of this study was to evaluate the variety (brown or golden flaxseed), presentation more effective (flax flour or grains) and the real benefits of flaxseed on oxidative status, glucose level and lipid profile in healthy human volunteers. For this, 48 volunteers were selected and instructed to ingest 40g of flaxseed daily fresh in the morning for 14 days. Venous blood was collected in fasting, anthropometric and blood pressure measurements were performed before and after the supplementation period. The results demonstrate that clinical parameters did not change significantly within 14 days of supplementation, but significant changes in markers of oxidative stress were observed. There was a significant effect of dietary intervention with grain flaxseed golden or brown in protecting plasma proteins and membrane lipids of harmful action of reactive species. This positive effect was not observed in supplementation with flour flaxseed golden or brown. This lack of result may be related to the content of flavonoids which shows a remarkable ability to neutralize reactive species. The plasma concentration of polyphenols significantly decreased after 14 days of supplementation. This result is possibly a direct consequence of the neutralization of reactive species generated by metabolism of linoleic and linolenic fatty acids present in flaxseed. The vitamin C increased after 14 days of taking flaxseed golden or brown, showing the presence of this vitamin in the seed. The data showed no change in the analysis of DNA damage by comet assay and micronucleus frequency. The antioxidant defense enzymes, superoxide dismutase, catalase and glutathione peroxidase, showed no significant changes in their activities after the supplementation period. Thus, the results indicate that the flaxseed in the form of grain in both varieties can be a valuable supplement assist in treatment of diseases that have as base free radicals.
Evaluation of the antioxidant and anti-genotoxic effects in vivo of linum seed usitatissimum l.
Keywords: Linum usitatissimum; Linhaça; Antioxidante; Parâmetro clínico; Linum usitatissimum; Flaxseed; Antioxidant; Clinical parameters